2012
DOI: 10.1038/nprot.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of human pluripotent stem cells to cerebral cortex neurons and neural networks

Abstract: Efficient derivation of human cerebral neocortical neural stem cells (NSCs) and functional neurons from pluripotent stem cells (PSCs) facilitates functional studies of human cerebral cortex development, disease modeling and drug discovery. Here we provide a detailed protocol for directing the differentiation of human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) to all classes of cortical projection neurons. We demonstrate an 80-d, three-stage process that recapitulates cortical devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
843
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 807 publications
(898 citation statements)
references
References 24 publications
23
843
2
1
Order By: Relevance
“…In the past decade, several protocols to convert hiPSCs into neurons have been developed [2][3][4][5][6][7][8] . However, these protocols are still limited in many ways.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several protocols to convert hiPSCs into neurons have been developed [2][3][4][5][6][7][8] . However, these protocols are still limited in many ways.…”
Section: Introductionmentioning
confidence: 99%
“…A major advance from traditional differentiation methods is the circumvention of embryoid body (EB) formation for more efficient and direct induction of neural progenitor cells (NPCs) and expansion of neurospheres [99][100][101][102]. For example, Lie et al proffers high yield production of NPCs from feeder-free iPSC aggregates cultured in mTeSR™1(Stem Cell Technologies) [99].…”
Section: Neural Differentiation Of Ipscs: Quality and Quantitymentioning
confidence: 99%
“…A more protracted method by Shi et al induces iPSCs over 90 days to excitatory "cortical projection" neurons, with intermediate "cortical primary" stem/progenitor cells formed within 2 weeks, followed by "early-born" neurons produced between 2-3 weeks, and "last-born" neurons arising as late as day 90 [100]. The method is based on a much earlier protocol of SMAD signalling inhibition [93], and is purportedly highly efficient and less variable among different cell lines due to replacing noggin with SMAD inhibitor dorsomorphin [100].…”
Section: Neural Differentiation Of Ipscs: Quality and Quantitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lou et al (2007) demonstrated that such stem cells contributed in the regeneration of damaged cells in the rat. Likewise, recovery of hair cells in vitro have been demonstrated in mice by application of fetal cochlea stem cells (Shi et al 2012;Savary et al 2007;Oshima et al 2007;White et al 2006;Doetzlhofer et al 2004). Also, embryonic and neural stem cells have been used to experimentally treat deafness in mice (Parker et al 2007; Corrales et al 2006).…”
Section: Introductionmentioning
confidence: 99%